An online mindfulness-based intervention influences the health-related quality of life of Indian children and adolescent during COVID-19 pandemic: a randomized controlled trial - Pal, Anirban; Mukhopadhyay, Purnava; Pal, Nidhi Dawar (International Journal of Contemporary Pediatrics, 2023)
Background: COVID-19 pandemic is endangering the psychosocial health of Indian children and adolescent. The psychosocial morbidity can get manifested as psychiatric diseases if not addressed properly. This study aims to see the effects of an online Mindfulness-based intervention on the health-related quality of life (HRQoL) of apparently healthy but ‘vulnerable’ children in Indian community, during the COVID-19 pandemic. Methods: A randomized controlled trial with 43 children and one of their interactive parents as participants from the community. An online eight-week Mindfulness program was selected as the psychosocial intervention. 22 participants in group M attended the Mindfulness program (parents in group PM) while 21 participants in group C attended placebo sessions (parents in group PC). The quantitative measure was the HRQoL, measured by the KIDSCREEN10 questionnaire. Qualitative data was in form of a response to a question “Which aspect of the mindfulness program appealed to you the most from your child’s perspective?” The post-program parent responses were analyzed on basis of some emergent themes. The statistical analyses used were independent samples t-test, Chi-square test and one-way analysis of variance (ANOVA) for the outcome variables. Results: The KIDSCREEN10 score significantly improved (p value <0.0001) in the cases (group M and PM), compared to the control groups. ‘Calm’ and ‘focus’ were the prominent emergent themes, reported by the parents post-program. Conclusions: The online mindfulness-based intervention positively impacts the health-related quality of life of Indian children and adolescents during the COVID-19 pandemic. The results need to be substantiated by further studies.